Three-dimensional printing in prosthetics: Method for managing rapid limb volume change. (October 2020) - Nickel, Eric; Barrons, Kyle; Hand, Barry; Cataldo, Alana; Hansen, Andrew
Background and Aim: During post-amputation recovery or rapid body mass change, residual limb volume can change quickly, requiring frequent adjustments or replacement of the socket to maintain fit. The aim of this pilot test was to evaluate the feasibility of using a three-dimensional-printed insert to extend the service life of a prosthetic socket after substantial residual limb volume loss. Technique: One research subject with a well-fitting transtibial prosthetic socket had an oversized socket fabricated to simulate substantial limb volume loss. The digital shapes of the oversized and well-fitting sockets were used to create a three-dimensional-printed insert to restore fit. Discussion: Two-minute walk test distance decreased when using the oversized socket without the insert, but not when using the socket with the insert. Socket comfort score was 8+ under all conditions. These results suggest that three-dimensional-printed inserts may be an effective method of extending the service life of prosthetic sockets when rapid limb volume loss occurs. Clinical relevance: Three-dimensional (3D) printing gives prosthetists a new tool to manage large volume changes without refabricating entire sockets. Sockets can be fabricated in anticipation of volume gain/loss, using replaceable 3D-printed inserts to maintain fit and comfort.